Gender disparities in the National Institutes of Health funding for hematologic malignancies and cellular therapies. Issue 7 (7th June 2022) - Siddiqui, Raheel Sufian; Chaudhary, Sibgha Gull; Shahzad, Moazzam; Anwar, Iqra; Hussain, Ali; Ahmed, Nausheen; Abhyankar, Sunil Hari; Shune, Leyla; Hematti, Peiman; Male, Heather; Khosa, Faisal; Lin, Tara; et al.
Abstract: We investigated gender inequality in the National Institutes of Health (NIH) funding for hematologic malignancies and cellular therapies (HMCT). The data were retrieved from the NIH Research Portfolio Online Reporting Tools (RePORT). In 2018–2019, 1834 grants totaling 799 million were awarded (men 71% vs. women 29%) to 975 principal investigators (PIs), including 680 (70%) male PIs and 295 (30%) female PIs. There was no significant gender difference in the mean grant amount per PI. Male PIs as compared to female PIs had a higher h-index (44 vs 31, p < 0.001), a higher number of publications (159.5 vs 94, p < 0.001), and higher years of active research (26 vs 21, p < 0.001). In multivariate analyses, a higher h-index independently predicted a higher mean grant amount per PI ( p = 0.010), and female PIs were independently less likely to have a higher h-index ( p < 0.001). Our study shows significant gender disparity in the NIH funding for HMCT research.